Long-term effects of executive function training among veterans with chronic TBI. (15th October 2019) - Novakovic-Agopian, Tatjana; Kornblith, Erica; Abrams, Gary; McQuaid, John R.; Posecion, Lainie; Burciaga, Joaquin; D'Esposito, Mark; Chen, Anthony J. W.
ABSTRACT: Objective : To investigate long-term effects of GOALS executive function training in Veterans with chronic TBI. In a recently completed study Veterans with chronic TBI showed improvement immediately post-GOALS but not control training on measures of executive function, functional task performance, and emotion regulation. We now examine the long-term maintenance of post-GOALS training changes in the same sample. Setting : San Francisco VA Health Care System (SFVAHCS), and VA Northern California Health-Care System (VANCHS) in Martinez. Participants and Design : 24 Veterans with chronic TBI were assessed at baseline, post-GOALS training, and long-term follow-up 6+ months following completion of training with a structured telephone interview, neuropsychological and complex functional performance measures, and self-report measures of daily and emotional functioning. Results : Participants reported an increased likelihood of involvement in competitive employment/volunteering at follow-up (61%) compared to baseline (26%; χ2 = 5.66, p < .01, ѱ = .35). Repeated measures MANOVAS indicated improvement on attention/executive function (F = 13.85, p < .01, partial η2 = .42), complex functional task performance (GPS Total: F = 9.12, p < .01, partial η2 = .38) and daily functioning (MPAI Total: F = 3.23, p < .05, partial η2 = .21), and reduction in overall mood disturbance (POMS Total: F = 3.42, p < .05, partial η2 = .22) at follow-up relative to baseline. Discussion : Training in attention regulation applied to participant-defined goals is associated with meaningful long-term improvement in cognitive skills, emotion regulation, and daily functioning in Veterans with chronic TBI.